Tetrakis[\(\mu\)3-2-(piperidin-1-yl)ethanolato]- tetrakis[chloridocopper(II)] - Luo , Mei; Huang , Yong-Hua; Zhang , Jing-Cheng (Progress in Chemical Science Research Vol. 6, 2023)
The tetranuclear compound, [Cu4(C7H14NO)4Cl4] is N,O-chelated by a piperidineethanolate anion and coordinated by a Cl— anion and two O atoms from neighboring piperidineethanolate anions in a distorted NO3Cl square-pyramidal geometry. The crytal structure is provided by single-crystal X-ray study, the crystal data can be listed as followings: T = 293 K; mean \(σ\)(C–C) = 0.015 A; R factor = 0.068; wR factor = 0.182; data-to-parameter ratio = 17.5.